The role of mesenchymal cells in cholangiocarcinoma - Sueca Comes, Mireia (2023)
The process of tumour formation and progression is highly influenced by the components of the tumour microenvironment (TME) through a mutual and dynamic crosstalk. Cholangiocarcinoma (CCA) is a highly desmoplastic tumour; however, the role of its reactive TME is not fully elucidated. Treatments are limited and often ineffective due to the lack of biomarkers for its early diagnosis and the lack of understanding of its molecular pathogenesis. Therefore, we believe that investigating the TME and its role in CCA progression could lead to more effective therapeutic treatments for managing this devastating cancer.